Figure 14-17 from: Beccacece H, Vincent B, Navarro F (2014) The type-material of Arctiinae (Lepidoptera, Erebidae) described by Burmeister and Berg in the collection of the Museo Argentino de Ciencias Naturales Bernardino Rivadavia (Buenos Aires, Argentina). ZooKeys 421: 65-89. https://doi.org/10.3897/zookeys.421.6666 - Beccacece, Hernan; Vincent, Benoit; Navarro, Fernando (Zenodo, 2014)
Figure 14-17 - 14 Lectotype female Ecpantheria kinkelini Burmeister 15 Lectotype male Ecpantheria anomala Burmeister 16 Lectotype male Antarctia severa Berg 17 Lectotype female Bombyx deserticola Berg.